Physical barriers faced by People with disabilities (PwDs) in shopping malls - Bashiti, Alaa; Abdul Rahim, Asiah (Elsevier Ltd., 2015)
This paper intends to discuss the issue of accessibility, connectivity and usability in the facilities that used by people with disabilities (PwDs) in shopping malls and the significance of the latest Malaysian standards (MS 1184:2014) Universal Design and Accessibility in the Built Environment-Code of Practice in evaluating shopping malls. Three case studies have been selected to evaluate accessibility of the shopping malls for PwDs which are Ikea in Damansara, Suria Kuala Lumpur convention Centre (KLCC) in Kuala Lumpur and Alamanda in Putrajaya. Both qualitative and quantitative methods will be applied in this study, Data were collected using semi structured interviews with visually-impaired person, hearing-impaired person, wheelchair user and crutches user to find out their perception on the level of accessibility of these buildings. Access audit and site observation were also carried out in assessing the building’s accessibility, connectivity, mobility and reachability.